IMPACTOS PSICOLÓGICOS DO ABUSO SEXUAL INFANTIL NA FASE ADULTA (REMUNOM, 2024)
Child sexual abuse is a public health problem with serious and long-lasting consequences in the lives of victims. This study aims to analyze the psychological impacts of sexual abuse in childhood and how these effects can manifest themselves in adulthood. To this end, a bibliographic research was carried out, the prevalence of child sexual abuse, its emotional and psychological consequences, and the strategies to support the victims were investigated, with a focus on psychotherapeutic interventions. It was found that sexual abuse can generate a series of psychological disorders, such as Post-Traumatic Stress Disorder (PTSD), depression and anxiety, which can last throughout life, in addition to negatively influencing interpersonal relationships and the victim's self-image.  Psychotherapy presents itself as an important resource to help victims reframe their traumatic experiences and resume a full life. The need for effective public policies and ongoing psychosocial support for these victims is also addressed.